Padronização das variáveis do marketing mix na internacionalização do varejo especializado: estudo comparativo nos mercados do Brasil e da Turquia - Tancsik, Luís Américo (2017)
The purpose of this study is to identify how the process of marketing mix variables standardization occurs outside the country of origin, in a specialized retailer. Initially a literature review was done to define the variables to be analyzed and which were the elements that compose each of them, both influenced by the specific characteristics of the retail companies. Also, in the literature review stage, it was possible to understand the relevance of the standardization process in the internationalization of retail and the lack of studies dealing with specialized retailers. A case study was structured with a retailer specialized in children's products, comparing the country of origin – Italy – with two company’s operations, one in Brazil and the other in Turkey. Data collection was done through in-depth, semi-structured interviews with executives from all three countries, as well as document analysis and field observation, with visits to the company's stores in Turkey and Brazil. The results obtained are in line with the standardization concept of variables, and the main variables, such as type of store, location and store ambiance are standardized. The results also indicate that not all the elements of a variable considered important are standardized, suggesting that the concept of continumm could also be applied to the elements that compose the variable.